Evaluasi Sistem Penyimpanan Obat Antibiotik dengan Menggunakan Metode Fifo dan Fefo di Gudang Farmasi Rumah Sakit X - Ghea Isna Anandani; Rismayanti Fauziah; Wempi Eka Rusmana (Cerdika: Jurnal Ilmiah Indonesia, 2022)
According to RI law no. 40 of 2009, a hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. Storage methods can be carried out by applying the FEFO and FIFO principles, depending on the unit size and alphabetical order. This study was conducted to determine the antibiotic drug storage system using the FIFO and FEFO methods in the pharmacy warehouse of Hospital X. The method used in this study was a descriptive and quantitative method with the data used were primary data derived from interviews in the hospital pharmacy warehouse. X. Based on the results of research that has been carried out at Hospital X from 14 respondents for results categorized as Good (100%) for results categorized as Bad (86%) while for results categorized as Poor (64%). So it can be concluded that based on the dosage form, it states that the storage of drugs that are in accordance with the dosage form is categorized as Good. Meanwhile, liquid preparations stored on the bottom shelf are categorized as poor. Based on the alphabet, it states that the storage of antibiotics is in accordance with the alphabet, categorized as Good. Antibiotics with generic names are complete in the drug warehouse and are categorized as poor. Based on FIFO, it is stated that the FIFO method is very effective in being applied in the pharmaceutical drug warehouse, which is categorized as good. Based on FEFO, it is stated that the FEFO method is very important to be applied in a good category of drug warehouse.